Optimizing Inventory Management in Food & Beverage Department Hotel - Rosalina Nur Annisa; Dodik Prakoso Suwandojo; Meiana Maulida Hikmawati (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2023)
The application of inventory management in the hotel's Food & Beverage (F&B) division is examined in this article. The F&B division struggles greatly to maintain ideal stock levels while assuring effective operations and lowering costs. The department uses a well-known inventory management model and seeks to balance the price of placing orders with the cost of maintaining inventory. The main ideas of Economic Order Quantity (EOQ) are covered in this article along with its advantages and some useful tips for using it in the F&B department. It is anticipated that the application of EOQ will improve inventory control, decrease stockouts and surplus inventory, and eventually increase profitability and customer satisfaction.Keywords: Food and beverage department, stock control, Economic Order Quantity (EOQ), inventory management, cost-cutting, and customer satisfaction.